Manufacturing Sectors in India: Outlook and Challenges. (2017) - Mehta, Yash; Rajan, A. John
Abstract: India is fast becoming one of the most lucrative options for manufacturing industry to prosper. This research was carried out to study the current manufacturing strategies implied by India for its growth in the manufacturing sector. An analysis was done on the factors which affect the manufacturing sector in different states across the country. Good infrastructure, compliance to tax & labour laws and meeting the desired environmental standards were some of the factors responsible for better performance of states like Gujarat and Andhra Pradesh." International Monetary Fund (IMF) raised a concern about the pace of the reforms which are being passed. They pointed out that Indian economy is facing "decelerating pace of reforms". Recently the long waited GST bill had been passed by the government of India which would enable an easy and a cost cutting flow of goods across different states of the country. It presents a wonderful opportunity for the manufacturing sector to re-establish the logistic sector of the country. A strong infrastructure is an essential ingredient for any manufacturing sector to grow. Keeping that in mind the government of India is investing a lot of funds in building a strong network of roads, rails and transport to foster the growth of the manufacturing sector. As many industrial corridors and road networks rapidly are being formed, this paper focuses on how these networks are catering to the growth of this sector. From this research we found out how new laws especially on land and labour coupled with constant improvement in the infrastructure is aiding India to emerge as the new manufacturing sector hub.